Construction with land: knowledge put at the service of the community of Cácota, Norte de Santander (REVISTA NODO, 2019)
The training of construction workers, professionals and the community in general in alternativeand traditional construction technologies such asthe one that uses land, in its different techniques,through methodologies that share knowledgehorizontally as “learning by doing”, responds tothe problem urgent to train capable techniciansin the conservation of the built heritage, to theneed to recover and give continuity to traditionaland tested construction systems, which allow toaddress the housing deficit and the construction ofa sustainable habitat.
Keywords: Construction workshop with earth; Alternative and appropriate construction technology; Participatory design